Understanding imposter syndrome: a comprehensive review - Kaur, Navjot; Sharma, Kamlesh K.; Gandhi, Tanya (International Journal Of Community Medicine And Public Health, 2025)
Imposter syndrome (IS) is defined as a psychological phenomenon consisting of feelings of inadequacy and a persistent fear related of being exposed as a fraud despite evident progress and accomplishments. The aim of this article is to provide an understanding of IS, exploring its origins, manifestations, IS in medical and nursing students, its impact, and potential strategies for coping and overcoming it. Drawing upon a wide range of psychological research, and case studies, the review sheds light on the complexities of IS and offers insights into its prevalence across different demographics and professions, especially among medical and nursing students. Additionally, the article discusses the potential role of societal pressures, perfectionism, and self-doubt in perpetuating imposter feelings.